EFFECT OF CHEMICAL ACTIVATION TREATMENTS ON PARTHENOGENETIC DEVELOPMENT OF IN VITRO MATURED BUFFALO OOCYTES - REENA, D; BALASUBRAMANIAN, S; DEVANATHAN, T G (The Indian Journal of Animal Reproduction, 2023)
This study was designed to investigate the effect of chemical activation treatments on parthenogeneticdevelopment of in vitro matured fresh (24 h) and aged (30 h) buffalo oocytes. Six trials were conducted eachwith control, ethanol and ionomycin activation treatments. In control group, none of the oocytes cleaved. In theethanol activation (EA) group, the cleavage rates of fresh and aged oocytes were 10. 75 ± 3.02 and 21.19 ±2.24, respectively and there was significant difference (P
Keywords: Buffalo; chemical activation; oocyte aging; parthenogenesis